(untitled) (Agroindustrial Science, 2022)
The objective of this research work was to characterize and identify multipattern clonal grafts with morphological, physicochemical, and health characteristics to obtain good yields and fruit pulp quality in soursop populations. The descriptor list for soursop, recommended by CORPOICA, was used to characterize the fruit and pulp of the clonal plants. For the quantitative and qualitative morphological characterization of the fruit, the statistical software InfoStat was used, and to determine the most outstanding characteristics of the pulp, the software SPSS Ver. 24 was used. The chemical analysis of the pulp was done by means of the non-parametric techniques of Kruskal Wallis. In the qualitative characterization of the pulp, 43.1% showed white and snow-white color, 42.1% had an acid flavor, 57.9% had a medium texture and 44.7% had a medium aroma and 36.8% had a high aroma, 50% proved to be semi juicy. The pH found ranged between 4.70 and 2.92, with respect to the total soluble solids expressed in ºBrix, averaging 17.10. It is concluded that there is genetic variability in qualitative and quantitative characters of the fruit and pulp in grafted clones and differences were found in the chemical analysis of the pulp of clonal plants.